2016
DOI: 10.1016/j.ajog.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Acute feTal behavioral Response to prenatal Yoga: a single, blinded, randomized controlled trial (TRY yoga)

Abstract: There was no significant change in fetal blood flow acutely after performing yoga for the first time in pregnancy. Yoga can be recommended for low-risk women to begin during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…This is in line with the randomised controlled study in which acute changes in fetal responses to yoga exercises were investigated. After a supervised one-off yoga session, no significant changes in fetal cardiovascular activity and umbilical artery blood flow were reported 95…”
Section: Moving Forward: Prenatal Relaxation Techniques and Their Effmentioning
confidence: 95%
“…This is in line with the randomised controlled study in which acute changes in fetal responses to yoga exercises were investigated. After a supervised one-off yoga session, no significant changes in fetal cardiovascular activity and umbilical artery blood flow were reported 95…”
Section: Moving Forward: Prenatal Relaxation Techniques and Their Effmentioning
confidence: 95%
“…Previous studies have not reported any maternal injuries during their study period in those who practiced yoga. 30,31 Risks to the fetus are also unknown and not well documented. A randomized controlled trial conducted by Babbar et al 31 assessed the acute fetal response to prenatal yoga.…”
Section: Risksmentioning
confidence: 96%
“…15 Short-term fetal tolerance to yoga exercises in pregnancy has been demonstrated. 15,31 The long-term effects of yoga on the fetus or neonate are unknown because of the paucity of reports in the literature. Fetal growthandbirthweightserveasmeasurable outcomes that reflect the health status of a pregnancy.…”
Section: Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 outlines the characteristics of the included studies and applies the frequency, intensity, time/duration and type (FITT) principle of exercise prescription across the studies. Ten of the included studies originated from India (14,16,17,(33)(34)(35)(36)(37)(38)(39) , eight from the USA (9,11,15,18,42,(43)(44)(45) and one each from China, Indonesia, Iran, Japan, Thailand and the UK. (46)(47)(48)(49)(50)(51) Twenty of the studies were RCTs, three were non-randomised control trials and one was a trueexperimental post-test only control group design.…”
Section: Study Characteristicsmentioning
confidence: 99%